Singlet-triplet energy gaps modulation of Diindeno [1,2-b: 1’2’-g] anthracene molecular family - Cárdenas Valdivia, Abel; Dressler, Justin J.; Kishi, Ryohei; Rudebusch, Gabriel E.; Ventura, Austin M.; Chastain, Brian E.; Gómez-García, Carlos J.; Zakharov, Lev N.; Nakano, Masayoshi; Casado-Cordón, Juan; Haley, Michael M. (My University, 2022)
Nowadays there is a large interest in organic materials based on diradical polycyclic aromatic hydrocarbons (PAHs) due to their unique properties, such as narrow frontier-orbital energy gaps, strong absorption in the visible spectrum, etc. However, the inherent diradical nature make these compounds with limited chemical stability giving rise to rapid decomposition under ambient conditions thus reducing their practical use. In recent years PAH diradicals that exhibit remarkable stability have been prepared thanks to the description of efficient synthetic routes to access them. One of these remarkable cases is the diindeno [1,2-b: 1’2’-g] anthracene, named as DIAn. DIAn is constituted by antiaromatic segments together with a central pro-aromatic structure. One of the important observable properties of diradicals is the singlet-triplet energy gap, ∆EST, which is intimately connected with the diradical character. The possibility of access to the molecular structure of diradicals is very valuable since properties such as the bond-order or the bond-length alternation of the mentioned moieties reveal the diradical content. Electronic and vibrational spectroscopies are alternative sources of structural information that often compensate the absence of solid-state structures. In this communication, we expand the studies of DIAn by introducing another aspect of the modulation of the ∆EST which concerns with: i) the extension of the terminal benzenes with another fused benzene (i.e., forming terminal napthalenes) and ii) with the isomerization resulting from the fusion topology of these terminal benzenes. We will present a UV-Vis-NIR and Raman spectroscopic study of the new compounds. The variation of the spectra within molecular family will be discussed in connection with the variation of ∆EST and with the diradical character of the new molecules.
Keywords: Intervalo de energía (Física); Espectroscopia Raman; Propiedades magnéticas; Singlet- Triplet Energy Gaps; Raman Spectroscopy; Diradicaloids PAH; Two electrons in the two-site model of diradicals; Magnetic properties